Effects of metals on activity and community of sulfate-reducing bacterial enrichments and the discovery of a new heavy metal-resistant SRB from Santos Port sediment (São Paulo, Brazil) - Zampieri, Bruna Del Busso [UNESP]; Nogueira, Elis Watanabe; de Oliveira, Ana Julia Fernandes Cardoso [UNESP]; Sánchez-Andrea, Irene; Brucha, Gunther (Springer Nature, 2022)
Sulfate-reducing bacteria (SRB) can be used to remove metals from wastewater, sewage, and contaminated areas. However, metals can be toxic to this group of bacteria. Sediments from port areas present abundance of SRB and also metal contamination. Their microbial community has been exposed to metals and can be a good inoculum for isolation of metal-resistant SRB. The objective of the study was to analyze how metals influence activity and composition of sulfate-reducing bacteria. Enrichment cultures were prepared with a different metal (Zn, Cr, Cu, and Cd) range concentration tracking activity of SRB and 16S rRNA sequencing in order to access the community. The SRB activity decreased when there was an increase in the concentration of the metals tested. The highest concentration of metals precipitated were 0.2 mM of Cd, 5.4 mM of Zn, 4.5 mM of Cu, and 9.6 mM of Cr. The more toxic metals were Cd and Cu and had a greater community similarity with less SRB and more fermenters (e.g., Citrobacter and Clostridium). Meanwhile, the enrichments with less toxic metals (Cr and Zn) had more sequences affiliated to SRB genera (mainly Desulfovibrio). A new Desulfovibrio species was isolated. This type of study can be useful to understand the effects of metals in SRB communities and help to optimize wastewater treatment processes contaminated by metals. The new Desulfovibrio species may be important in future studies on bioremediation of neutral pH effluents contaminated by metals.
Keywords: Bioremediation; Desulfovibrio; Metal removal; Metal resistance; Metals; Sulfate-reducing bacteria